EFFICACY OF PREOPERATIVE MISOPROSTOL IN REDUCING HEMORRHAGE DURING ABDOMINAL MYOMECTOMY - Khan, Qudsia Qazi; Liaqat, Nazia; Shafqat, Tanveer; Bawar, Shandana (Journal of Ayub Medical College Abbottabad, 2020)
Background Uterine myomas are most common non-cancerous tumours in reproductive period. The fertility preserving surgery, i.e., myomectomy as compared to hysterectomy, is associated with massive blood loss due to dissection of huge fibroids making it technically difficult procedure. Misoprostol (a uterotonic) is an effective option amongst different interventions used to reduce intraoperative blood loss during myomectomy. This randomized control trial investigated effectiveness of single dose of rectal misoprostol given preoperatively in reducing intraoperative blood loss during abdominal myomectomy. Methods Fifty Patients undergoing abdominal myomectomy were selected for the study. Twenty-five patients were given 800 micrograms misoprostol per rectally half an hour before surgery while rest received placebo, i.e., control group. Number and weight of surgical packs were recorded both Pre and post operatively to assess blood loss. Preoperative and 24 hrs postoperative haemoglobin was also recorded. Data analysed by SPSS-20. Results: Mean of age, parity and myoma size were not statistically different between the two groups. However intraoperative blood loss (as measured by weighing and counting number of swabs used) and postoperative haemoglobin after 24 hours were significantly different between two groups with p-value <0.01. Conclusion: Single dose of misoprostol given preoperatively via rectal route is effective in reducing intraoperative blood loss during abdominal myomectomy. Misoprostol must be used in different doses and routes in order to investigate its effectiveness in reducing intraoperative blood loss. Keywords: Preoperative misoprostol; Abdominal myomectomy; Intra operative ;Blood loss